ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BILANGAN BULAT DI KELAS VII SMPN MODEL TERPADU MADANI PALU - Tobigo, Yekri Sandi; Paloloang, Baharuddin; Pathuddin, Pathuddin (Universitas Tadulako, 2022)
This study aims to determine the types of errors made by high-ability students and low-ability students in solving integer arithmetic operations. This type of research is qualitative research. The subjects of this study were taken 2 of 31 students of grade VII Hasan Bahasoan SMPN Model Terpadu Madani Palu, which consisted of one high-ability student and one low-ability student. The results of this study were (1) errors made by the Constitutional Court subject in the form of procedural errors, namely the Constitutional Court subject did not arrange hierarchical and systematic steps in solving integer arithmetic operations. (2) errors made by the subject IW in the form of a conceptual error, namely the subject IW did not understand the concepts, terms and theorems of integer arithmetic operations in solving problems. IW subjects also made procedural errors, namely IW subjects were unable to manipulate the steps in solving problems.